Mode Tim Dalam Media Quizizz Mampu Meningkatkan Motivasi dan Keaktifan Belajar Peserta Didik Kelas VI SDN Tanjunganom - Muhamad Lutfi Hidayat; Gunawan Sridiyatmiko (UM Purwokerto Press, 2022)
The purpose of this research is to increase the motivation and activeness of students in the learning process. Through team mode, each student will contribute points to be accumulated into group scores. This research is a Classroom Action Research. The subjects of this study were students of class VI SDN Tanjunganom, Banyuurip District, Purworejo Regency totaling 25 children. Techniques Data collection is done with a questionnaire, observation. The data analysis technique used a quantitative descriptive technique with percentages. The results showed that 1) Quizizz Media team mode can increase students' motivation; this is indicated by the increasing number of students who have a minimum high motivation, from 40% in the pre-cycle, to 88% in the first cycle and 92% in the second cycle; 2) Team mode in Media Quizizz can increase student activity; this is indicated by an increase in the number of students who are included in the minimal activity category either from 44% in the pre-cycle, to 64% in the first cycle and 92% in the second cycle. The results of the research on motivation and activity as a whole have met the minimum criteria specified at 75% so that the research was stopped in cycle II.